Impact of Caregiving for Dementia Patients on Healthcare Utilization of Caregivers - Rahman, Ateequr (Pharmacy (Basel), 2019)
The elderly, whom are vulnerable to the physical, mental and chronic diseases of aging, are the fastest growing segment of the US population. Dementia is of particular concern in this population, and caregivers of people with dementia are subjected to psychological, physical, emotional and functional stress. The purpose of this study was to investigate the impact of caregiving for dementia patients on health care services utilization of caregivers and to examine if caregivers utilize more healthcare services than the control group. The study recruited a total of 143 people in control and non-control groups through non-probability convenience sampling. The control group (non-caregivers) comprised of 71 people, whereas the experimental group (caregivers) consisted of 72 participants. The focus of the study was the health care utilization questionnaire, asking the caregiver about the frequency of specific health care services utilization—including medication use in the last six months, on the scale from 0 to 10. Results were statistically significant for each of the healthcare service utilization when comparing caregivers to the control group. By providing adequate support and assistance in form of support groups, we can alleviate caregivers’ burden and more effectively address the needs of caregivers—thereby reducing the utilization of healthcare services.